Bacterial nanocellulose : a sophisticated multifunctional material - Gama, Miguel; Gatenholm, Paul.; Klemm, D. (Dieter). (Boca Raton, FL : CRC Press, 2013)
'The first book dedicated to the potential applications and unique properties of bacterial cellulose (BC), this seminal work covers the basic science, technology, and economic impact of this bulk chemical as well as the companies and patents that are driving the field. It reviews the biosynthesis and properties of BC, including genetics and characterization; discusses the advancing technology as it relates to product development, bioreactors, and production; and analyzes the economic impact of BC on a diverse range of industry applications, including materials and biomaterials, biological and polymer sciences, and electromechanical engineering'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Bacteria -- Metabolism; Acetobacter xylinum; Cellulose -- Synthesis